The potential influence of atherogenic dyslipidemia on the severity of chronic Chagas heart disease - Peverengo,Luz (2016)
SUMMARY Introduction: chronic Chagas heart disease (CCHD) is the most common manifestation of American Trypanosomiasis, causing about 50,000 deaths annually. Several factors bear correlation with the severity of CCHD. However, to our knowledge, the assessment on the contribution of major cardiovascular risk factors (CRF), such as hypertension and atherogenic dyslipidemia (AD) to CCHD severity is scarce, despite their well-established role in coronary artery disease, heart failure and stroke. Objective: to explore the potential relationship of blood pressure and AD with the clinical profile of patients with CCHD. Methods: we performed a cross-sectional study in T. cruziseropositive patients categorized according to a standard CCHD classification. All individuals were subjected to complete clinical examination. Autoantibodies induced by T. cruzi were assessed by ELISA. Results: we observed that Atherogenic index (AI) levels rose significantly in relation to the severity of the CCHD stage, with CCHD III cases showing the highest values of AI. Furthermore, those patients with globally dilated cardiomyopathy with reduced ejection fraction showed higher levels of AI. In regard to autoantibodies, anti-B13 also showed relation with the severity of the disease. Conclusion: we observed that AI correlated with CCHD stages and contributed, in association with anti-B13 antibodies and age, to the prediction of systolic heart failure.